«The story of my life» by G. A. Gapon: how and why it was written - Konstantin Kremenetski (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
The “Story of my Life” by Georgiy Gapon was published in English in Great Britain in November 1905 and was simultaneously translated into French and Russian. This book has been often used ever since in describing the course of events in St. Petersburg on January 9, 1905. The editor of the Soviet edition of the book, A. S. Shilov, paid attention to the fact that the description of the events of January 9 was largely based on publications from Russian emigrant revolutionary newpapers. However, the authenticity of the book was never questioned. Detailed examination of the English original and its comparison with the Russian version of the book demonstrate that the English text is entirely based on a careful compilation of numerous texts from contemporary English, French and Russian newspapers and magazines. It contains inconsistencies as to the basic facts of Gapon’s biography. The text was written by the English author George Perris with collaboration with his Russian colleague David Sockice. Both were members of the Society of Friends of Russian Freedom and were actively involved in the Russian revolutionary movement. The book was presented to the public as an authentic autobiography of Gapon. The publication of the book was part of propaganda eff orts to consolidate in public opinion the version of events of January 22 created by British and French newspapers and to counterbalance the offi cial Russian explanation of the nature of the riot on January 9, 1905.